THE EFFECT OF DRAGON FRUIT PEEL JUICE (Hylocereus sp) IN DRINKING WATER ON EGGS QUALITY OF LOHMANN BROWN AGE OF 48-51 WEEKS - M. F., ulum; Dewi, G. A. M. K.; Wirapartha, M. (Jurnal Peternakan Tropika; Vol 7 No 3 (2019): Issue 7 No. 3 - 2019; September - December 2019, 2019)
The study aimed to examine the effect of giving dragon fruit peel juice (Hylocereus sp.) through drinking water on the quality of Lohmann brown eggs was conducted at Teaching Farm Campus Bukit Jimbaran, Badung, Bali during 45 days. The experimental design used was a Completely Randomize Design (CRD) with three treatments and five replications, each replication using three Lohmann brown layer age of 48-51 weeks. The treatments are Lohmann Brown was given drinking water without dragon fruit peel juice as a control (R 0 ), Lohmann Brown was given drinking water contain 1% dragon fruit peel juice (R 1 ), and Lohmann Brown was given drinking water contain 3% dragon fruit peel juice (R 2 ). The variables observed in this study included egg weight, egg index, egg shell weight, egg shell thickness, egg pH, egg yolk color, and  egg haugh unit. The results showed that the egg weight in the treatments R 0 , R 1 , R 2 was significantly different (P <0.05), while the other variables (egg index, egg shell weight, egg shell thickness, egg yolk color, egg haugh unit, and egg pH) showed results that were not significantly different (P> 0.05). Based on the results of this study it can be concluded that 1% and 3% dragon fruit peel juice in drinking water can increase egg weight and does not affect on egg shell thickness, egg shell weight, egg yolk color, egg haugh unit, and egg pH of Lohmann Brown age of 48-51 weeks. Keywords : Lohmann Brown, dragron fuit peel juice, drinking water, egg quality .